Interdisciplinary Decision Making in Hemorrhagic Stroke Based on CT Imaging—Differences Between Neurologists and Neurosurgeons Regarding Estimation of Patients' Symptoms, Glasgow Coma Scale, and National Institutes of Health Stroke Scale - Wagner, Andrea; Schebesch, Karl-Michael; Isenmann, Stefan; Steinbrecher, Andreas; Kapapa, Thomas; Zeman, Florian; Baldaranov, Dobri; Grauer, Oliver; Backhaus, Roland; Linker, Ralf A.; Schlachetzki, Felix (Frontiers in Neurology, 2019)
Background and purpose: Acute intracerebral hemorrhage (ICH) requires rapid decision making towards neurosurgery or conservative neurological stroke unit treatment. In a previous study, we found overestimation of clinical symptoms when clinicians rely mainly on cerebral computed tomography (cCT) analysis. The current study investigates differences between neurologists and neurosurgeons estimating specific scores and clinical symptoms. Methods: Overall 14 neurologists and 15 neurosurgeons provided clinical estimates and NIHSS as well as GCS based on cCT images and basic information of 50 patients with hypertensive and lobar ICH. Subgroup analyses were performed for the different professions (neurologists vs. neurosurgeons) and bleeding subtypes (typical location vs. atypical). The differences between the actual GCS and NIHSS scores and the cCT-imaging-based estimated scores were depicted as Bland-Altman plots and negative and positive predictive value (NPV and PPV) for prediction of clinical relevant items. ΔNIHSS-points (ΔGCS-points) were calculated as the difference between actual and rated NIHSS (GCS) including 95% confidence interval (CI). Results: Mean ΔGCS-points for neurosurgeons was 1.16 (95%-CI: -2.67 to 4.98); for neurologists 0.99 (95%-CI: -2.58 to 4.55), p=0.308; mean ΔNIHSS-points for neurosurgeons was -2.95 (95% CI: -12.71 to 6.82); for neurologists -0.33 (95% CI -9.60 to 8.94), p<0.001. NPV and PPV for stroke symptoms were low, with large differences between different symptoms, bleeding subtypes and professions. Both professions had more problems in proper rating of specific clinic-neurological symptoms than rating scores. Conclusion: Our results stress the need for joint decision making based on detailed neurological examination and neuroimaging findings also in telemedicine.